Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00421-007-0570-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory responses during three repeated incremental exercise tests in sickle cell trait carriers

Abstract: This study investigated the cardioventilatory responses during heavy exercise in sickle cell trait carriers (SCTc) and subjects with normal hemoglobin (control group). Eight SCTc and six control subjects repeated three incremental exercise tests (Iet) separated by 10-min recoveries. Cardioventilatory parameters were analyzed at rest and during the first and third Iet. No significant difference in the ventilatory parameters [notably, maximal oxygen uptake (VO2max) and the ventilatory thresholds] was observed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…10,13,[27][28][29][30][31] In contrast, our results do not demonstrate differences in baseline or longitudinal changes in fitness by SCT status, which is consistent with other studies that have also shown no difference in maximal oxygen uptake or key determinants of fitness, including lactate production and ventilatory threshold, in individuals with and without SCT. [32][33][34][35] We also found no difference in autonomic nervous system function by SCT status, using our measure of heart rate recovery after exercise. However, variability in methodology used to define fitness and autonomic nervous system function may explain discrepancies in findings across studies.…”
supporting
confidence: 47%
“…10,13,[27][28][29][30][31] In contrast, our results do not demonstrate differences in baseline or longitudinal changes in fitness by SCT status, which is consistent with other studies that have also shown no difference in maximal oxygen uptake or key determinants of fitness, including lactate production and ventilatory threshold, in individuals with and without SCT. [32][33][34][35] We also found no difference in autonomic nervous system function by SCT status, using our measure of heart rate recovery after exercise. However, variability in methodology used to define fitness and autonomic nervous system function may explain discrepancies in findings across studies.…”
supporting
confidence: 47%
“…27 Similarly, several studies using incremental maximum exercise demonstrated no difference between SCT carriers and normal controls in regard to VO 2max , ventilatory threshold, or hemodynamic parameters. [28][29][30][31] Despite such experimental evidence for normal fitness levels of SCT carriers, some authors believe that SCT carriers might be hindered from highly competitive sports. Le Gallais et al observed no SCT carriers among Abidjan halfmarathoners.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of V02max (gold standard for aerobic fitness) between SCT carriers and non-SCT controls yielded no differences (62,75,77), even under acute mild, moderate, or severe hypoxic conditions (63,(97)(98)(99). When SCT carriers and non-SCT controls were compared on other criteria of aerobic fitness (ventilatory threshold and lactate threshold), no differences existed between the two populations (39,60,66). Similarly, when SCT carriers and controls repeated three incremental exercise bouts to exhaustion, interspaced with 10 min of recovery, no differences in any cardiorespiratory parameters were detected (60).…”
Section: Athletic Performance With Sctmentioning
confidence: 94%
“…When SCT carriers and non-SCT controls were compared on other criteria of aerobic fitness (ventilatory threshold and lactate threshold), no differences existed between the two populations (39,60,66). Similarly, when SCT carriers and controls repeated three incremental exercise bouts to exhaustion, interspaced with 10 min of recovery, no differences in any cardiorespiratory parameters were detected (60). However, Vincent et al (94) found lower cytochrome C oxidase activity in muscle fibers from SCT carriers relative to controls, which could limit oxidative energy metabolism and lower aerobic capacity in this population (23).…”
Section: Athletic Performance With Sctmentioning
confidence: 99%